HUBUNGAN ANTARA KOORDINASI MATA TANGAN, KEKUATAN PEGANGAN DAN KESEIMBANGAN DENGAN KETEPATAN MEMUKUL BOLA BISBOL PADA MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI JAKARTA (2003) - Taufik Rihatno (Gladi : Jurnal Ilmu Keolahragaan, 2017)
Abstarct The purpose of study is to find out the relationships between hand eye coordination, grip strenght with balance in baseball hitting accuracy. The research was conducted at faculty of sport and science, state university of Jakarta with 60 samples, which were selected by simple random sampling. The finding are as follows : (1) there is a positive correlation between hand eye coordination and baseball hitting accuracy, (2) there is a positive correlation between grip strenght and baseball hitting accuracy, (3) there is a positive correlation between balance and baseball hitting accuracy, (4) there is a positive correlation between hand eye coordination, grip strenght, and balance simultaneously with baseball hitting accuracy. It can be concluded that baseball hitting accuracy could be enhanced by increasing hand eye coordination, grip strength, and balance individually as well as simultaneously. Keywords: hand eye coordination, grip strenght with balance, baseball